Search, engineering, and applications of new oxidative biocatalysts. (12th May 2014) - Martínez, Angel T.; Ruiz‐Dueñas, Francisco J.; Gutiérrez, Ana; del Río, José C.; Alcalde, Miguel; Liers, Christiane; Ullrich, René; Hofrichter, Martin; Scheibner, Katrin; Kalum, Lisbeth; Vind, Jesper; Lund, Henrik
Abstract Most industrial enzymes are hydrolases, such as glycosidases and esterases. However, oxidoreductases have an unexploited potential for substituting harsh (and scarcely selective) chemical processes. A group of basidiomycetes are the only organisms degrading the aromatic lignin polymer, enabling the subsequent use of plant polysaccharides. Therefore, these fungi and their ligninolytic peroxidases are the biocatalysts of choice for industrial delignification and oxidative biotransformations of aromatic and other organic compounds. The latter also include oxygenation reactions, which are catalyzed with high regio/stereo selectivity by fungal peroxygenases. In search for novel and more robust peroxidases/peroxygenases, basidiomycetes from unexplored habitats were screened, and hundreds of genes identified in basidiomycete genomes (in collaboration with the DOE JGI). The most interesting genes were heterologously expressed, and the corresponding enzymes structurally‐functionally characterized. The information obtained enabled us to improve the enzyme operational and catalytic properties by directed mutagenesis. However, the structural‐functional relationships explaining some desirable properties are not established yet and, therefore, their introduction was addressed by 'non‐rational' directed evolution. Then, over 100 oxidative biotransformations were analyzed. Among them, it is noteworthy to mention the regio/stereo selective hydroxylation of long/short‐chain alkanes (a chemically challenging reaction), epoxidation of alkenes, and production of hydroxy‐fatty acids. Concerning aromatic oxygenations, the regioselective hydroxylation of flavonoids, and stereoselective hydroxylation/epoxidation of alkyl/alkenyl‐benzenes were among the most remarkable reactions, together with enzymatic hydroxylation of benzene (as an alternative for harsh chemical process). Finally, peroxidases and peroxygenases also showed a potential as delignification biocatalysts and in the decolorization of contaminant dyes from textile industries. © 2014 The Authors. Biofuels, Bioproducts and Biorefi ning published by Society of Chemical Industry and John Wiley & Sons, Ltd.